2020
DOI: 10.1136/jitc-2020-001355
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of tumor-infiltrating NK and T cells highlights IL-15 stimulation and TIGIT blockade as a combination immunotherapy strategy for soft tissue sarcomas

Abstract: PurposeGiven the unmet need for novel immunotherapy in soft tissue sarcoma (STS), we sought to characterize the phenotype and function of intratumoral natural killer (NK) and T cells to identify novel strategies to augment tumor-infiltrating lymphocyte (TIL) function.Experimental designUsing prospectively collected specimens from dogs and humans with sarcomas, archived specimens, and The Cancer Genome Atlas (TCGA) data, we evaluated blood and tumor NK and T cell phenotype and function and correlated those with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
77
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(80 citation statements)
references
References 52 publications
(53 reference statements)
2
77
1
Order By: Relevance
“…Hence, detailed analyses would be truly beneficial in STSs. While intratumoral NK cells of STSs exhibit numerous activation and exhaustion markers, peripheral NK cells in STS patients were observed as functionally impaired [86,87]. Patients undergoing NK-cell based immunotherapies mostly profit from administration of IL-15, a potent NK cell activator, while anti-NKG2A therapy is still lacking among clinical trials in STSs [125,126].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, detailed analyses would be truly beneficial in STSs. While intratumoral NK cells of STSs exhibit numerous activation and exhaustion markers, peripheral NK cells in STS patients were observed as functionally impaired [86,87]. Patients undergoing NK-cell based immunotherapies mostly profit from administration of IL-15, a potent NK cell activator, while anti-NKG2A therapy is still lacking among clinical trials in STSs [125,126].…”
Section: Discussionmentioning
confidence: 99%
“…Judge et al further demonstrated that intratumoral NK cells express more activation and exhaustion markers as compared to peripheral blood NK cells [87]. Furthermore, ex vivo stimulation with IL-15 further increased both activation and exhaustion markers in intratumoral and peripheral blood NK cells [87]. The authors observed a significant upregulation of TIGIT receptor and, therefore, suggested a therapeutic potential of TIGIT blockade together with IL-15 therapy [87].…”
Section: Natural Killer (Nk) Cell Infiltrationmentioning
confidence: 98%
See 1 more Smart Citation
“…Importantly, the therapeutic effect of TIGIT antibody blockade was found to be NK cell-dependent as antibody-mediated NK cell depletion in mice 24 h prior to TIGIT blockade abrogated the positive effects of TIGIT antibody treatment [ 104 ]. Similar studies in human peripheral blood NK cells showed that TIGIT blockade enhanced their anti-tumor activity against soft-tissue sarcoma and ovarian carcinoma tumor targets in vitro, and significantly, reduced tumor burden of mice with ovarian carcinoma xenografts [ 105 , 106 ]. These encouraging pre-clinical results have led to the initiation of multiple clinical trials using monoclonal anti-TIGIT antibodies alone or in combination with other checkpoint inhibitors (NCT02913313, NCT04570839].…”
Section: Strategies To Overcome the Tumor Microenvironmentmentioning
confidence: 94%
“…RLI also enhanced the anti-tumor activity of PD-1 antagonist [ 98 ]. TIGIT has emerged as an additional checkpoint inhibitor for novel combinatorial therapy with IL-15 [ 99 ].…”
Section: Il-15 In Combination Therapy For Cancermentioning
confidence: 99%